Nurses’ Knowledge of Infection Control Practices in Intensive Care Unit in Saudi Arabia - Nawal A. Alissa; Azhar Alqadi (SAGE Open)
This study aimed to assess nurses’ knowledge to control infection transmitted by intensive care units. Specifically, the study focused on the constructs of nurse’s knowledge, such as guidelines, personal practices, and preventive practices to control contagious diseases in intensive care units’ patients. A descriptive cross-sectional study design was utilized in this study. A convenience sample of 209 nurses from intensive care units was included in the analysis. The study was carried out at the intensive care units of five hospitals of the Aseer Health Authority, Saudi Arabia. The self-administrated questionnaire was adapted to assess the knowledge of safety guidelines, personal safety measures, and preventive practices among the study participants. The findings suggested a significant knowledge gap regarding the nurses’ knowledge of guidelines and prevention practices. F statistics showed a significant gender-based differences in nurses’ knowledge about guidelines, personal practices, and healthcare-associated infections prevention practices ( F  = 9.78, p  < .05; F  = 13.45, p  < .05; F  = 2.47, p  < .05, respectively). There is little information available about standards, behavior patterns, and ways to stop infections from spreading to intensive care units’ patients. In order to illustrate significant results and provide additional recommendations for future research, this work attempted to close the gap between previous findings and the findings of this investigation. The study highlighted the fundamental relevance of infection control practices in healthcare, particularly in intensive care units, in ensuring patient safety.